USING SERIOUS GAMES TO RECRUIT, INTEGRATE AND TRAIN YOUR EMPLOYEES: AN EXPLORATORY STUDY OF PRACTICES - Oihab Allal-Chérif (European Scientific Journal, ESJ, 2014)
Serious games are used in various sectors, including car industry, defense, aeronautics, pharmaceuticals, healthcare, banking, and media. They seem to have reinvigorated and expanded the field of corporate simulations. Different from e-learning tolls, they are relying on new information and communications technologies; they have borrowed from the universe of video games to offer players/learners a new kind of experience. Much more than a simple fashion, serious games have become ubiquitous in the field of recruitment, ranging from the integration of new employees to interactive training, benchmarking and institutional communications. Serious games have had a major effect on human resource management in the companies that use them, and their generalization augurs some major and lasting changes in this function. The present text aims to study several cases of serious games and demonstrate the different ways in which these games are used as well as their impact on individual and collective performance and on human resource management practices. The article will pursue a prospective approach that also gives consideration to potential developments affecting these gaming-educational platforms and the corporate roles they can be expected to fulfill in the future.